2010
DOI: 10.4995/wrs.2010.778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early feed restriction on performance and health status in growing rabbits slaughtered at 2 kg live-weight

Abstract: ABSTRACT:The effect of a time-limited access to the feeders (8 h per d from 9:30 to 17:30) on fattening performance and health status was studied in rabbits reared until 2 kg live-weight as typical in the Spanish market. For this purpose, the same diet (10.5 MJ digestible energy/kg, 38.9% neutral detergent fi bre and 18.4% crude protein on dry matter basis) was used over two consecutive trials. A total of 192 growing rabbits (96 in each trial) were weaned at 35 d and assigned to 2 different feeding treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
4
34
1
4
Order By: Relevance
“…However, both heavy and light rabbits were within standard ranges for being accepted by Spanish slaughterhouses. Other authors also found this reduction in final weight when animals were fed under a restricted diet in comparison with AD-fed ones (Gidenne et al, 2009a and2009b;Romero et al, 2010). It is important to state that in the present study the restricted regimen was maintained during the entire growing period, whereas in the case of Romero et al (2010) the restriction was applied only during 2 weeks just after weaning.…”
Section: Discussionmentioning
confidence: 54%
“…However, both heavy and light rabbits were within standard ranges for being accepted by Spanish slaughterhouses. Other authors also found this reduction in final weight when animals were fed under a restricted diet in comparison with AD-fed ones (Gidenne et al, 2009a and2009b;Romero et al, 2010). It is important to state that in the present study the restricted regimen was maintained during the entire growing period, whereas in the case of Romero et al (2010) the restriction was applied only during 2 weeks just after weaning.…”
Section: Discussionmentioning
confidence: 54%
“…Martignon et al (2009) confirmed that the favourable impact of the restriction originated clearly from the quantity of feed offered and not from the distribution procedure. However, this favourable impact of a reduced intake seems to occur only during the restriction period, and does not continue when animals return to AL intake (Gidenne et al, 2009a;Romero et al, 2010). Similar results were also obtained by reducing the intake level through a time-limited access to drinking water (Boisot et al, 2004;Verdelhan et al, 2004;El Maghraby, 2011).…”
Section: Effect Of a Post-weaning Feed Restriction On Digestion And Dmentioning
confidence: 67%
“…For instance, for light slaughter weights (as in Spain) the economic value of restriction strategies may be reduced (Romero et al, 2010). In conclusion, beneficial effects of an intake limitation in growing rabbits have been proved in experiments and in field conditions.…”
Section: Conclusion and Prospectsmentioning
confidence: 85%
See 1 more Smart Citation
“…This can be accomplished either using feed with low nutrient density or feed with a high structural carbohydrate content (Rodríguez- Romero et al, 2011;Martínez-Vallespín et al, 2011, by limiting the intake of pelleted all-mash feed until postnatal week 8 (Schlolaut et al, 1978;Schlolaut and Lange, 1979;Gidenne et al, 2003Gidenne et al, , 2009), or by actively restricting the feeding time (Schlolaut and Lange, 1990;Romero et al, 2010). If despite the premature developmental state of the digestive system high growth rates are to be achieved by feeding pelleted all-mash feed ad libitum starting at postnatal day 17, or if the young have access to the mother's food, it is necessary to reduce the proliferation of pathogens by adding bacteriostatic or bactericidal food supplements.…”
Section: Dietmentioning
confidence: 99%